2005
DOI: 10.1103/physrevb.72.085345
|View full text |Cite
|
Sign up to set email alerts
|

Many-body interactions in a quantum wire in the integer quantum Hall regime: Suppression of the exchange-enhancedgfactor

Abstract: The collapse of Hall gaps in the integer quantum Hall liquid in a quantum wire is investigated. Motivated by recent experiment [Pallecchi et al. PRB 65, 125303 (2002)] previous approaches are extended to treat confinement effects and the exchanged enhanced g factor in quantum wires. Two scenarios for the collapse of the ν = 1 state are discussed. In the first one the ν = 1 state becomes unstable at B (1) cr , due to the exchange interaction and correlation effects, coming from the edge-states screening. In the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…9 The effect of the many-body interactions on the spin splitting in quantum wires in the IQH regime has been a subject of numerous studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] These studies have focused on various aspects of 2DEG in confined geometries including the structure of compressible/incompressible strips, suppression or enhancement of the g factor, subband spin splitting, spatial spin separation, and others. We, however, have not been able to find in the literature any systematic quantitative treatment of the magnetoconductance of the structures at hand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The effect of the many-body interactions on the spin splitting in quantum wires in the IQH regime has been a subject of numerous studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] These studies have focused on various aspects of 2DEG in confined geometries including the structure of compressible/incompressible strips, suppression or enhancement of the g factor, subband spin splitting, spatial spin separation, and others. We, however, have not been able to find in the literature any systematic quantitative treatment of the magnetoconductance of the structures at hand.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the exchange and correlations effects leading to the strong enhancement of the electron g factor above its bulk value 9 . The effect of the many-body interactions on the spin splitting in quantum wires in the IQH regime has been a subject of numerous studies 10,11,12,13,14,15,16,17,18,19,20,21,22,23 . These studies have focused on various aspects of 2DEG in confined geometries including the structure of compressible/incompressible strips, suppression or enhancement of the g factor, subband spin splitting, spatial spin sepa-ration and other.…”
Section: Introductionmentioning
confidence: 99%
“…A powerful tool to study electron-electron interaction and spin effects in quantum wires is the mean-field approach such as the Hartree-Fock (HF) and the spin density functional theory (DFT) [1]. A number of studies based on these approaches addressing various aspects of interacting electrons in the IQH regime in quantum wires have been reported recently [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, in some cases different studies produce different results and findings reported in some studies are not recovered in others.…”
Section: Introductionmentioning
confidence: 99%